Evaluasi Perencanaan dan Pengadaan Obat dengan Dana JKN di Puskesmas Rambipuji Jember - Norcahyanti, Ika; Firandi, Adelia; Ramadhani, Nuril Izzati Farihatur; Rachmawati, Sinta; Rachmawati, Ema; Aryani, Dhita Evi; Wardhani, Firdha Aprillia; Kusumaningrum , Yunita Dyah (Faculty of Pharmacy, University of Jember, 2024)
Public Health Center is a health facility that organizes drug management activities, including planning and procurement activities. Evaluation needs to assess the success of achieving the objectives and results of the action. Indicators that can use are efficiency indicators published by the Ministry of Health of the Republic of Indonesia and efficiency indicators developed by Pudjaningsih. Rambipuji Public Health Center with spending funds for the most significant drug procurement in Jember Regency in 2020. Therefore, it is necessary to evaluate the results that can improve the quality of service in the next period. This research aims to determine the results of the evaluation of drug planning and procurement with JKN funds at Rambipuji Public Health Center for 2020. This research is descriptive, primary data through interview results. Secondary data includes total funds available, drug procurement funds, Drug Usage Reports, and Drug Demand Sheets for drugs purchased through JKN funds and stock cards. The data is analyzed descriptively, presented in the form of tables supported by interview results. The results showed that the Government of Indonesia had governed drug planning and procurement activities with JKN funds. The percentage indicator of available funds compared to the general funds needed is 114.26%. The percentage indicator of drug procurement fund allocation is 3.46%. Results on percentage indicator procurement conformity with the reality of the use of each drug item amounted to 133.33% and on the procurement frequency indicator of each drug item once a year. Through this research, it can be concluded that the evaluation results on indicators of the efficiency of drug planning and procurement activities at Rambipuji Public Health Center have not been by established standards. This matter was influenced by several factors, including a decrease in the number of patient visits due to the COVID-19 pandemic, changes in the organizational structure in the Jember Health Office that resulted in the frequency of procurement activities only once throughout 2020, and the absence of government regulations that regulate in more detail about the percentage of JKN funds allowed for drug procurement activities.